A Geochemical Model of Fluids and Mineral Interactions for Deep Hydrocarbon Reservoirs. (16th July 2017) - Li, Jun; Ahmed, Raheel; Zhang, Qian; Guo, Yongfan; Li, Xiaochun
Abstract : A mutual solubility model for CO2 -CH4 -brine systems is constructed in this work as a fundamental research for applications of deep hydrocarbon exploration and production. The model is validated to be accurate for wide ranges of temperature (0–250°C), pressure (1–1500 bar), and salinity (NaCl molality from 0 to more than 6 mole/KgW). Combining this model with PHREEQC functionalities, CO2 -CH4 -brine-carbonate-sulfate equilibrium is calculated. From the calculations, we conclude that, for CO2 -CH4 -brine-carbonate systems, at deeper positions, magnesium is more likely to be dissolved in aqueous phase and calcite can be more stable than dolomite and, for CO2 -CH4 -brine-sulfate systems, with a presence of CH4, sulfate ions are likely to be reduced to S 2− and H2 S in gas phase could be released after S 2− saturated in the solution. The hydrocarbon "souring" process could be reproduced from geochemical calculations in this work.